2011
DOI: 10.1002/cphc.201100121
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism Exhibited by Nanoparticles of Noble Metals

Abstract: Gold nanoparticles with average diameters in the range 2.5-15 nm, prepared at the organic/aqueous interface by using tetrakis(hydroxymethyl)phosphonium chloride (THPC) as reducing agent, exhibit ferromagnetism whereby the saturation magnetization M(S) increases with decreasing diameter and varies linearly with the fraction of surface atoms. The value of M(S) is higher when the particles are present as a film instead of as a sol. Capping with strongly interacting ligands such as alkane thiols results in a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Using the leading-in-, field-dependent contribution (15) to the free energy, the grand-canonical contribution to the magnetic moment [see Eq. (5)] is given by the semiclassical expression…”
Section: Semiclassical Thermodynamic Formalism For Noninteractinmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the leading-in-, field-dependent contribution (15) to the free energy, the grand-canonical contribution to the magnetic moment [see Eq. (5)] is given by the semiclassical expression…”
Section: Semiclassical Thermodynamic Formalism For Noninteractinmentioning
confidence: 99%
“…An aspect that attracted considerable attention over the last two decades is the very unusual magnetic behavior of gold nanoparticles. Indeed, while bulk gold is diamagnetic, several experiments have shown that ensembles of gold nanoparticles capped with organic ligands can present a ferromagneticlike behavior of the magnetization, up to room temperature or above [6][7][8][9][10][11][12][13][14][15][16]. Other samples show a paramagneticlike behavior [11,12,[16][17][18][19][20][21][22] and some others a diamagnetism which is typically stronger than in the bulk [6,8,11,19,23].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been previously observed in thiol-capped GNPs and seems to be directly associated with the magnetic mechanisms present in these systems. 9,35 Furthermore, low T magnetic interactions are evidenced in the non-zero magnetic moment for H = 0. Regarding the GNPs size, the presence of remnant magnetization and coercive field could not be related with an inner magnetic domain structure.…”
Section: -B That M(h/t) Curves Deviates From This Behavior and Hystementioning
confidence: 98%
“…Au, Ag, Cu, Pd or Pt). 7,8,9 Although some works have proposed alternative mechanisms, such as self-sustained persistent currents of conduction electrons, at this moment there is general consensus about the orbital nature of this magnetic moment, 1,10 The appearance of magnetization in capped GNPs was proposed to be associated with a spin symmetry breaking related with the 5d and 6s electrons of the Au atoms involved in the chemical bond with the ligands. The presence of the capping agents at the surface changes the number of uncompensated spins, which in turn modifies the relative spin densities at the Fermi energy, thus creating a non-zero magnetic moment.…”
Section: Introductionmentioning
confidence: 99%
“…XMCD has also demonstrated the ferromagnetic contribution of copper and silver in thiol-capped nanoparticles [2]. Their saturation magnetization could be related to the strength of metal-ligand binding [11] even if that is still open to debate [12]. Ferromagnetism of uncapped gold or silver nanoparticles was however observed at room temperature [13,14] and theoretical studies have predicted ferromagnetism for clusters of bare noble metals [15e17].…”
Section: Magnetic Properties Of Noble Metals Nanoparticlesmentioning
confidence: 99%